Perancangan Aplikasi Perhitungan Analisa Beban Kerja Teknisi Telekomunikasi dan Navigasi Penerbangan - Setiyo Prabowo, Achmad (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2019)
At the moment technician workload analysis (ABK) has been implemented by Airnav Indonesia with partial method based on location of work Unit using calculation application such as Spreed Sheet/Excel on computer. In order to facilitate such calcullations need to be designed an application that can store all data in one server and easy to access so that in a short time can be known the number of Technician gap. The purpose of this research is to conduct application design calculation of ABK technician and database of the number of aviation technicians required based on the number of flight equipment that is Simulation of ABK flight calculation at an airport. This research is an experimental research in application creation and literature study. Troubleshooting methods using qualitative and quantitative descriptions based on regulations related to flight navigation organizing. The result of this design application is to facilitate the officers of the flight navigation inspectors in conducting inspections and will be very helpful to the Airnav party in the calculation of the needs of the aviation engineer gap analysis. Utilization of this application is intended to assist the calculation of the needs of the technician so as to provide input to the policy makers and the implementation of technician activities in the field/workload of technicians according to the standard conditions imposed.